Segmental mesenteric bowel infarction secondary to embolization intercostal arteries - Palacio, José L; Rodríguez, José L; Tiscornia, Eduardo; Delgado, Alicia; Colet, Andrés; Bianchi, Carlos (Cirugía del Uruguay, 1990)
The authors present a case of mesenteric vascular occlusion as a comp/ication of selective arteriography with embolization of intercostal arteries used as treatment for recidivistic hemoptysis. The indications, contraindications and complications of the procedure are analyzed, as we/1 as the therapeutical surgery emp/oyed when faced with this exceptional situation. They emphasize the importance of e/ose surveyance of the patient for some hours after the procedure.